Assessing Chemical Intolerance in Parents Predicts the Risk of Autism and ADHD in Their Children - Raymond F. Palmer; David Kattari; Rodolfo Rincon; Claudia S. Miller (MDPI AG, 2024)
Background: We sought to replicate our 2015 findings linking chemical intolerance in parents with the risk of their children developing autism and/or ADHD. Drawing upon our 2021 discovery of a strong association between chemical intolerance and mast cells, we propose an explanation for this link. Methods: In a population-based survey of U.S. adults, we used the internationally validated Quick Environmental Exposure and Sensitivity Inventory (QEESI) to assess symptom severity and chemical intolerance. Parents were asked how many of their biological children had been diagnosed with autism and/or ADHD. Results: Parents with chemical intolerance scores in the top versus bottom tenth percentile had 5.7 times the risk of reporting a child with autism and 2.1 times for ADHD. Conclusions: High chemical intolerance scores among parents of children with autism, coupled with our 2021 discovery of mast cell activation as a plausible biomechanism for chemical intolerance, suggest that (1) the QEESI can identify individuals at increased risk, (2) environmental counseling may reduce personal exposures and risk, and (3) the global rise in autism and ADHD may be due to fossil-fuel-derived and biogenic toxicants epigenetically "turning on" or "turning off" critical mast cell genes that can be transmitted transgenerationally. It is important to note that this study was observational in nature; as such, further research is needed using controlled trials to confirm causality and explore the proposed mechanism.